PENGEMBANGAN E-LKPD BERBASIS DISCOVERY LEARNING MENGGUNAKAN APLIKASI ADOBE ACROBAT 11 PRO EXTENDED PADA MATERI KESETIMBANGAN ION DAN pH LARUTAN GARAM UNTUK KELAS XI SMA/MA SEDERAJAT - Aulia Augustha; Susilawati Susilawati; Sri Haryati (UIR Press, 2021)
This study aims to develop E-LKPD based on Discovery Learning using the Adobe Acrobat 11 Pro Extended application on the ion balance and pH of salt solution for class XI SMA / MA, to determine the validity of E-LKPD based on aspects of content feasibility, characteristics of Discovery Learning, linguistic aspects, presentation aspects, graphic aspects, size, cover design, content design and knowing the user's response to the developed E-LKPD. This development research is a type of Research and Development (R&D) with the Plomp development model. The data collection instruments are in the form of validation sheets given to two material validators and two media validators, as well as user response questionnaires for teachers and students. After two revisions, the validity results obtained by the material validator on the content feasibility aspect were 94.44%, the characteristic aspects of Discovery Learning were 95.83%, the presentation aspects were 90%, the linguistic aspects were 90.62% and the graphic aspects were 93.5% which each of these aspects is included in the valid criteria. Furthermore, the results of data analysis obtained validity by the media validator on the graphic aspect which included the E-LKPD size of 100%, the cover design was 90.63%, and the content design was 94.32%, each of which was categorized as valid. E-LKPD which has been declared valid by the validator is tested one by one on 3 students who have studied the ion balance and pH of the salt solution. Then ask for a response questionnaire to 3 chemistry teachers and 20 students. The results of the teacher's response were 95.55% including very high and practical criteria, the results of students' responses were 90.75% including interesting criteria. Based on the results of data analysis, it can be concluded that the E-LKPD based on Discovery Learning using the Adobe Acrobat 11 Pro Extended application produced was validated and can be used in high school chemistry subjects on ion balance and pH of salt solution.